The Impact of Digital Transformation on the Efficiency of Project Implementation in the Private Sector in the Kingdom of Saudi Arabia (International Journal of Financial, Administrative and Economic Sciences, 2024)
The research aims to identify the role of digital transformation in implementing projects in the private sector in the Kingdom of Saudi Arabia by improving the efficiency and effectiveness of implementation and project management processes through the use of modern technologies and digital technology. It also aims to improve competitiveness and promote innovation in the private sector. The results of the study found that digital transformation greatly affects all aspects of work in the private sector, from internal operations and management to product development. Digital transformation helps companies adapt to technology developments and better meet customer needs. By integrating advanced technologies such as artificial intelligence, big analytics, and cloud computing, companies can enhance their operations and make informed decisions. Customer interaction can also be improved through the use of digital technology to facilitate the customer experience. And provide better services. However, the report also points out challenges related to digital transformation, such as the necessary investment in technology and the impact of changes to traditional ways of working. 'Digital transformation also requires developing employee skills and providing the necessary support to achieve change. Overall, the study of digital transformation in the private sector highlights the importance of investing in technology and developing effective digital strategies to drive innovation and promote sustainable growth.
Keywords: Digital Transformation; Project Management; Private Sector; Kingdom of Saudi Arabia